Stem cell governance and ethics - Aziz, Mohammad Firdaus Bin Abdul (Routledge studies in Asian law., 2025)
"This book explores the ethical and governance concerns of stem cell technology, taking a comparative approach between countries of differing socio-economic status. The book provides a typology of different stem cell types and discusses key ethical issues surrounding the use of human stem cells in research. Topics covered include the moral status of human embryos, various religious perspectives, and the challenges posed by unproven stem cell interventions. The book also examines the existing governance frameworks in the UK, Singapore, and Malaysia, identifying the laws, guidelines, and advisory bodies established to address the identified ethical issues. Applicable lessons on establishing robust regulatory frameworks, fostering public trust, and ensuring responsible research practices are outlined. By providing a comparative analysis of the interplay between ethics, governance, and the socio-economic contexts of these three commonwealth countries, this book will interest health law, research ethics and bioethics scholars"--